Strategies for Gait Retraining in a Collegiate Runner with Transfemoral Amputation: A Case Report - Jillian Santer; Stephanie MacDonald; Katherine Rizzone; Shawn Biehler; Tanya Beiswenger (North American Sports Medicine Institute, 2021)
# Background More than fifty percent of people with limb amputations participate in sports or physical activity following amputation. Athletes with limb amputations may face additional challenges including phantom limb pain (PLP), psychological barriers, prosthetic complications, and gait abnormalities. Prevalence of PLP in the general amputee population is estimated to be as high as 85%. Despite the high prevalence of PLP, there is little research regarding the use of gait training as a treatment for PLP among both the general amputee population and athletes. # Case Description A 20-year old female collegiate track and field athlete presented with phantom knee pain brought on with running. The athlete demonstrated deficits in core and hip strength as well as decreased single leg stability bilaterally. Running gait analysis revealed circumduction with the prosthesis for limb advancement and increased vaulting with push off on the sound (uninvolved) limb. Gait retraining strategies were implemented to address video analysis findings and create a more efficient running gait and address phantom limb pain symptoms. # Outcomes Rehabilitation and gait retraining strategies were effective in improving several clinical and functional outcomes in this case. Significant improvements were noted in PLP, running gait mechanics, and the patient's psychological and functional status as measured with a standardized outcome tool, the Patient-Reported Outcomes Measurement Information System^®^ (PROMIS^®^). # Discussion Running gait training following amputation could be a crucial component of rehabilitation for athletes in an attempt to lessen pain while running, especially in those experiencing phantom limb pain (PLP). Utilization of a multidisciplinary team in the gait retraining process is recommended. There is a need for further research to determine the effects of running gait retraining for management of PLP in athletes with amputation. # Level of Evidence 5